DAMPAK MENU SEPINGGAN TERHADAP KONSUMSI DAN TINGKAT KECUKUPAN ENERGI SERTA ZAT GIZI LAIN PADA SISWA SD - Tiurma Sinaga; Clara M. Kusharto; Budi Setiawan; Ahmad Sulaeman (Jurnal Gizi dan Pangan, 2012)
The objective of this study was to analyze the effect of one dish meal breakfast on dietary intake and adequacy level of energy and other nutrients of elementary school children. The study used pre-experimentalone-group pretest-posttest design and was conducted from March to May 2011 at Kebon Kopi 2 Public ElementarySchool in Bogor City. The total number of sixty two elementary students were fully participated in this study, most of them were girls aged 11 years old. The Ethical Approval for this study was obtained from Komisi Etik Badan Penelitian dan Pengembangan Kesehatan No. KE.01.05/EC/301/2011. The study showed that there was significant difference before and after giving one dish meal breakfast as school feeding among the elementary school children (pKey words: one dish meal, breakfast school, dietary intakes, nutrient adequacy, elementary school children